Strategi Penggembangan Usaha Tani Mentimun di Kebun Perktek Universitas Nusa Nipa Indonesia - Aprinus Rizaldi Mari; Sarlina Noni (Jurnal Ilmiah Wahana Pendidikan, 2022)
Cucumber (Cucumis Sativus L.) is a horticultural plant originating from Asia, specifically from India (Rukmana, 1994). In 1882, de Condolle included this plant in the list of native plants of India. The data collected in this study are primary data and secondary data. Primary data is data obtained through direct interviews with consumers using questionnaires that have been prepared previously. While secondary data is data obtained from literature searches such as books, internet, thesis, data from the Central Statistics Agency (BPS) of Sikka Regency and other agencies related to this research. Strengths in cucumber development strategy: have organizational structure and vision, clear mission, good road and transportation access, available production facilities and infrastructure, supportive land conditions for cucumber cultivation, can make organic fertilizers and vegetable pesticides, good quality organic cucumbers. Weaknesses in the cucumber development strategy, namely: not having a good planting plan, unstable organic cucumber production, lack of promotional activities. Opportunities in cucumber development strategy.